Contextual Teaching and Learning Strategies on Student Engagement - Niken Anjelita; Vike Aprilianin Marwintaria Saputri; Hendri Ardianto (International Journal of Science and Applied Science: Conference Series, 2025)
This study aims to examine the effect of Contextual Teaching and Learning (CTL) strategies on student engagement in the learning process at the junior high school level. CTL is a learning approach that links subject matter to the real-life contexts of students, thereby encouraging active participation and deeper understanding. Although the CTL approach has been widely applied in various educational contexts, there is still a gap in research that specifically examines its impact on overall student engagement, especially when viewed from cognitive, emotional, and behavioral aspects simultaneously. This study uses a quantitative approach with a survey method. Data collection techniques were carried out using a Likert scale questionnaire that had undergone validity and reliability tests. The research sample consisted of 94 ninth-grade students at SMP Negeri 21 Pesawaran who were selected using total sampling. Data analysis was performed using simple linear regression to determine the extent of the influence of CTL strategies on student engagement in the learning process. The results showed that CTL strategies had a positive and significant influence on student engagement (p < 0.05). In terms of cognitive aspects, students showed improvement in critical thinking, material exploration, and problem solving. Emotional aspects showed an increase in interest, motivation, and a sense of responsibility for learning. Meanwhile, in terms of behavior, students were more actively involved in discussions, demonstrated good group cooperation, and were disciplined in participating in learning activities. The CTL strategy is also in line with Buddhist teachings, such as in the Kalama Sutta and Sigalovada Sutta, which emphasize reflective, meaningful learning and respect for the role of the teacher. Thus, CTL is recommended as an effective approach to improving the quality of student engagement in the classroom.